THE IDEAS AND THE PROJECTS OF THE MILITARY AUTHORITIES IN THE CONTEXT OF THE INTEGRATION OF THE NORTH CAUCASUS INTO THE RUSSIAN STATE (THE END OF XVIII - AT THE BEGINNING OF XIX C.) - T. Kolosovskaya (Гуманитарные и юридические исследования)
The article deals with the projects and ideas about the issue of the North Caucasus integration into the Russian Empire at the end of the XVIII - the beginning of the XIX centuries developed by the region’s military authorities.